Formulasi Dan Evaluasi Sediaan Sirup Antipiretik Ekstrak Daun Jeruk Nipis (Citrus aurantifolia L.) - Hanuf Nuzzaibah; Nur Ermawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Citrus aurantiifolia L. is a medicinal plant. Citrus aurantiifolia L as a traditional medicine is based very closely on the concentration of active ingredients, namely flavonoids, which have antipyretic (fever) effects. The aim of this study was to determine the effect of the concentration of Citrus aurantifolia L. as antipyretic on the physical properties of the syrup preparation and to determine the physical properties of the syrup preparation from the 3 formulations. to come up with the best formula. This type of research is experimental research. Citrus aurantiifolia L by This type of research is empirical research. Citrus aurantiifolia L by immersion method. The syrup preparations were formulated in 3 formulations with different concentrations of Citrus aurantiifolia L, namely 5%, 7.5% and 10%. The body properties of the syrup were tested, namely organoleptic, pH, clarity, viscosity, infusion volume, homogeneity and pleasure. Data analysis to check the physical properties of the syrup is described and presented clearly and in tabular form. The results show that the concentration of Citrus aurantiifolia L does not affect physical properties such as organoleptic, pH, clarity, volume transferred, viscosity and homogeneity. However, it makes a significant difference from the density test, i.e. the higher the extract concentration the higher the density value and conversely, the lower the extract concentration the higher the density value. low separately. Of all the recipes that met the criteria for linden leaf extract concentration, the best one for making syrup was Formula 3 (10%).